The Impact of Blended Learning on Self-Concept, Motivation, and Self-Efficacy in Mathematics Performance - Marin, Raul; Bolen-Amparo, Janice (Journal of Interdisciplinary Perspectives, 2025)
This causal research examined how blended learning influences the relationship between students’ self-concept, motivation, self-efficacy, and performance in Basic Calculus. It was undertaken to address the difficulties and poor performance of the students in Basic Calculus utilizing the promising benefits of blended learning instruction. This study aimed to determine the direct and indirect effects of blended learning on mathematics performance, as well as the mediating effects of blended learning on self-concept, motivation, and self-efficacy about mathematics performance. A survey was conducted with 220 STEM senior high school students to assess their self-concept, motivation, self-efficacy, and perceptions of blended learning. At the same time, their fourth-quarter exam scores reflected their performance. Correlational analysis revealed that self-concept, self-efficacy, and perceptions of blended learning were significantly associated with mathematics exam results. Path analysis revealed that self-concept, self-efficacy, and blended learning have significant positive direct effects on mathematics performance. Results showed that blended learning instruction can significantly predict improved achievement of mathematical concepts in introductory calculus among students. Mediation analysis revealed that self-concept and self-efficacy had a positive impact on performance, but blended learning did not significantly mediate these relationships. Motivation did not directly affect performance and was not mediated by the blended learning approach. These findings suggest that blended learning may not have a strong influence on math performance in this setting, highlighting the need to explore other factors that impact blended learning as a mediating variable on learning outcomes.